Muslim fashion business development strategy through digitalization in Medan City - Dimas Rafli Muharsya; Isnaini Harahap; Rahmat Daim Harahap (Pusat P2M Politeknik Negeri Batam, 2026)
This study aims to analyze strategies for developing Muslim fashion businesses through digitalization in Medan City. The research background is based on the rapid growth of digitalization, the rising awareness of modest fashion, and the increasing use of social media and online marketplaces by entrepreneurs. This research employed a qualitative method with a SWOT analysis approach, involving interviews with 10 Muslim fashion business owners. The findings reveal that digitalization significantly contributes to expanding market reach, improving consumer interaction, and facilitating transactions through social media and e-commerce. The main strengths are creative digital content and the adoption of modern payment systems, while weaknesses include limited digital literacy, low promotional budgets, and basic business management practices. Major opportunities come from the rise of online shopping, government support, and the growing demand for halal products. On the other hand, the main threats include intense competition, changing social media algorithms, and the rapid shift of fashion trends. This study concludes that the development of Muslim fashion businesses in Medan holds great potential if entrepreneurs can adapt to digitalization, strengthen branding, and enhance digital literacy through collaboration and training.